Communicating Statistical Results to Non-Statistician (2018)
In this write up, the researcher has stated that different statistical methods are meant for spécifie purposes and that Chi-square is meant to measure association, t-test is for measuring significance différence, while F-test is meant to détermine significant différence when we haue more than two groups and AFIOVA is meant for measuring the significant différence when we haue pre-score and post-score most especially when we carry out an experimental study. Corrélation and Régression analysis is meant for détermination of relationship between two or more uariables and for prédiction purpose. Therefore, there are seuen factors to be put into considération in the course of chosen appropriate test statistics in the course of analysing data. The factors are: research design, hypothesis/ research question wordings, past research work, nature and data arrangement, and scales of measurement which the data to be analysed belong to, by Consulting the experts and finally by considering the research topic/title. Finally, the researcher concluded that for anybody to make meaning from the computer printout analysis, one must understand the usefulness of degree of freedom, p-ualue and leuel of significance.